2019
DOI: 10.1021/acs.analchem.9b04505
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF2 Binds to 5-Methylcytosine in RNA and Modulates the Maturation of Ribosomal RNA

Abstract: Supporting InformationThe Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acs.analchem.9b04505. Detailed experimental procedures for Western blot, bisulfite sequencing, Northern blot, structure-based docking, and electrophoretic mobility shift assay; LC-MS/MS quantification data; and Western blot images (PDF) A list of proteins with relative binding ratios toward m 5 C-over C-containing RNA identified from SILAC-based affinity screening experiments with the use of lysate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 56 publications
0
49
0
Order By: Relevance
“…There is no mammalian protein domain currently known to bind N4mC; but MettL15 introduces N4mC in rRNA ( 62 ). However, the DUF55 domain of human thymocyte nuclear protein 1 (THYN1; also known as Thy28) shares a structural fold with the YTH domain ( 63 , 64 ), and has been suggested to bind DNA containing modified cytosine ( 65 ), while YTHDF2 binds 5mC in RNA ( 66 ). We note that the methyl groups of N4mC and N6mA share their location on the exocyclic amino groups of cytosine (at N4) and adenine (at N6) (Figure 6D ), and the MTases responsible for these two types of amino (N4-cytosine and N6-adenine) methylation belong to the same MTase family group ( 4 , 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is no mammalian protein domain currently known to bind N4mC; but MettL15 introduces N4mC in rRNA ( 62 ). However, the DUF55 domain of human thymocyte nuclear protein 1 (THYN1; also known as Thy28) shares a structural fold with the YTH domain ( 63 , 64 ), and has been suggested to bind DNA containing modified cytosine ( 65 ), while YTHDF2 binds 5mC in RNA ( 66 ). We note that the methyl groups of N4mC and N6mA share their location on the exocyclic amino groups of cytosine (at N4) and adenine (at N6) (Figure 6D ), and the MTases responsible for these two types of amino (N4-cytosine and N6-adenine) methylation belong to the same MTase family group ( 4 , 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…This lower affinity, coupled to the scarcity of both marks in mRNAs, leaves the actual occurrence and phenotypic impact of this "integration" as a question still to be answered. If confirmed, also other YTH domain-family proteins could behave similarly (Dai et al 2018b;Seo and Kleiner 2020;Dai et al 2020), as might be expected given their observed redundancy (Zaccara and Jaffrey 2020). One may thus wonder how these mechanisms could induce or affect pathological states (Meier et al 2016;Kadumuri and Janga 2018;Christofi and Zaravinos 2019;Huang et al 2020b).…”
Section: Interplaymentioning
confidence: 55%
“…Recently, new data Cold Spring Harbor Laboratory Press on January 3, 2021 -Published by rnajournal.cshlp.org Downloaded from suggested that different epitranscriptomic marks could coexist on the same transcript, and that a potentially widespread cooperative and competitive interplay could control the RNA fate, likely through RBPs (Dassi 2017). While the extent of this crosstalk is still unclear, several research groups described potential, mostly correlative, occurrences of such mechanisms (Li et al 2017a;Xiang et al 2018;Sokołowski et al 2018;Wei et al 2018a;Dai et al 2018b;Huang et al 2019;Seo and Kleiner 2020;Dai et al 2020). For instance, both m 6 A and m 5 C methylation sites were found in a specific region of the p21 mRNA.…”
Section: Interplaymentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence showed that YTHDF2, as a member of m6A "readers", played a significant role in multiple diseases, such as hematopathy and cancers [19][20][21]. Besides, significant progress had been made in fully understanding the role of m6A modifications in mRNA decay [22], pre-ribosomal RNA (rRNA) processing [23], and so on. These mechanisms were associated with diverse physiological and pathological processes, such as regulating inflammatory response [24], inducing pluripotent stem cells [25], adipogenesis [19].…”
Section: Introductionmentioning
confidence: 99%